The growth and development of dairy heifers fed a low, high and ad libitum allocation of milk replacer : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatū, New Zealand - Groenendijk, Mattes (Massey University, 2019)
Feeding calves more milk has been shown to increase their pre-weaning growth rate and is associated with improved lifetime performance, but few studies have determined the effect of providing greater milk allowance on the feed intake and growth of heifer calves in New Zealand dairy farming systems. The objective of this study was to determine the effect of 3 different milk replacer (MR) allowances when allocated via automated feeding machines on the feed intake, growth, mammary gland development and grazing behaviour of dairy heifers (Holstein- Friesian x Jersey) in a pastoral system. Calves were allocated MR at either a low allowance, fed at 10% of initial body weight (BW) (LA; n = 67), a high allowance, fed at 20% of initial BW (HA; n = 65) or an ad libitum allowance (ADLIB; n = 66). Weaning began after 69 days on the study by gradually reducing MR allowance over 14 days, so that weaning was concluded by 83 days. All calves had free access to pelleted calf starter via automatic feeders until 121 days, and to ryegrass hay from 21 to 91 days. Calves were put outdoors and given access to pasture at 91 days. Calves that were fed more MR had greater total dry matter intake and greater growth rate before weaning (ADLIB > HA > LA; P < 0.01), but ADLIB calves had lower intake of calf-starter and lower growth rate in the first 5-weeks after weaning than HA and LA calves (P < 0.01). At 6 months of age, ADLIB and HA calves were heavier than LA (P < 0.05), but there was no difference in BW at 10 months of age. Pre-weaning growth rate was positively associated with BW at 6 months of age (R2 = 0.37; P < 0.01) but was not related to post- weaning growth rate. Pre-weaning growth of the mammary parenchyma, as measured by ultrasonography, was greater in LA than ADLIB calves (P < 0.05) but there was no difference in the mammary fat pad or total gland growth. A subset of calves (n = 28) had their behaviour monitored on 4 occasions over a 5-week period, beginning a day after being given access to pasture. One day after being given access to pasture, ADLIB calves spent more time grazing than LA calves, and LA calves spent more time ruminating than HA and ADLIB calves (P < 0.05). There was no difference among treatments in grazing behaviour at subsequent observations. This study demonstrates that group-housed crossbred heifer calves have greater pre-weaning growth rates when fed more milk (10% of initial BW vs 20% of initial BW vs ad libitum feeding), and maintain this weight advantage to 6 months, but not to 10 months of age when grazing pasture. The impact of increased pre-weaning growth rate and the effect of differences in pre-weaning mammary gland development on future lactation performance of heifers in a pastoral system require further investigation.
Keywords: Heifers; New Zealand; Growth; Development; Dairy cattle; Feeding and feeds; 300301 Animal growth and development